ANALYSIS OF THE IMPACT OF THE HIGH SCHOOL DOUBLE TRACK PROGRAMME ON STUDENT SKILL AND CHARACTER DEVELOPMENT - Haniatur Rofiqoh Umar; Yosi Mariana; Sudarmiatin; Mokhammad Nurruddin Zanky (Jurnal Penelitian Progresif, 2026)
The Double Track High School Program, created by the East Java Provincial Government aims to simultaneously provide students with character and vocational competencies. However, previous research findings on the impact of this program are still fragmented, making it difficult to gain a comprehensive understanding of its "two-way impact." The impact of the program on the development of students' vocational skills and character is the objective of this research. A Systematic Literature Review (SLR) was used, which included the identification, assessment, and interpretation of fourteen selected journals that met the inclusion criteria. The research results show that the program is implemented through four systematic stages: preparation, planning, execution, and testing. The main fields of work for this program are culinary arts, fashion, multimedia, makeup, computer science and accounting, and light vehicle engineering. The results show that this program not only helps students acquire technical skills aligned with SKKNI and DUDI but also instills ethical-religious values, independence, entrepreneurship, and self-reliance. Although the Double Track Program faces operational constraints and produces graduates with "two competencies," namely being job-ready and having a strong character, the results show that this program is effective in producing strong graduates. However, further research is needed on how effective this program is at absorbing students.